Digestive disease interventions - Kapoor, Baljendra S.; Lorenz, Jonathan (Thieme, 2018)
Comprehensively covers the rich spectrum of radiologic digestive disease interventions Greater understanding of gastrointestinal disease has resulted in an evolving array of minimally invasive and noninvasive techniques. Significant advances have maximized patient comfort, improved clinical outcomes, and minimized morbidity. Interventional radiologists are integral to the management of patients with a wide range of digestive disorders, often providing a critical or sole therapeutic option. The field has evolved from a procedure-based radiology subspecialty to a patient-based, clinical specialt.